ENHANCING HISTORICAL THINKING SKILLS THROUGH DIGITAL LEARNING MODULES: A STUDY OF SECONDARY SCHOOL HISTORY EDUCATION IN MALAYSIA - M. Khairi Mahyudin; Sam Hermansyah (Satmata: Journal of Historical Education Studies, 2025)
In the context of 21st-century education, history as a subject faces the challenge of remaining relevant, engaging, and pedagogically effective. This study aims to develop a technology-integrated history curriculum and digital learning module for Malaysian secondary schools, addressing the gap between conventional teaching methods and the technological competencies required by modern learners. Using the Design-Based Research (DBR) methodology, the study was conducted through four main phases: needs analysis, design and development, implementation, and evaluation. The curriculum and digital module were designed to align with the national syllabus, incorporating multimedia tools such as videos, augmented reality (AR), interactive infographics, and online quizzes to support student-centered learning. The module was validated by curriculum and educational technology experts, followed by implementation in six secondary schools involving 700 students and history teachers. Quantitative data were collected through surveys and pre-post tests, while qualitative feedback was obtained from teacher interviews and classroom observations. The results showed high acceptance across all participating schools, with average ratings above 4.5 out of 5 in key areas such as engagement, content clarity, usability, and alignment with curriculum objectives. Statistical analysis using ANOVA confirmed that the module was consistently effective across diverse educational contexts. The novelty of this research lies in its systematic integration of technology not as an accessory, but as a central component of curricular design. The findings offer a replicable model for history education reform, particularly in Southeast Asian or other developing country contexts. This study contributes to the global discourse on digital pedagogy by demonstrating how thoughtful curriculum planning and technology use can transform traditional classrooms into dynamic, interactive, and inclusive learning environments.